Knowledge and attitudes of the pharmacists, prescribers and patients towards generic drug use in Istanbul - Turkey - (:unkn) unknown (My University, 2012)
The use of generic drugs has increased significantly in recent years. Since generic drugs are available at a lower cost, they provide an opportunity for savings in drug expenditure. Thus, use of generic drugs is encouraged especially in developing countries. There are only a few studies concerning the perceptions and attitudes of the healthcare providers and patients towards generic drug use. METHODS: The present study was conducted by a face to face questionnaire in the Kadikoy district of Istanbul in April 2010. From randomly chosen respondents, 68 pharmacists, 56 prescribers and 101 patients consented to participate in the study. RESULTS: Thirty one and 32 % of the pharmacists and prescribers, respectively, expressed that they believed that the generics did not differ from the original drugs, whereas only 24% of the patients believed so. Forty percent of the pharmacists and 82% of the prescribers told that they were unsure about the bioequivalence of the generics. Ten percent of the patients claimed that they immediately accept generic substitution by the pharmacist, while 26% accepted it if it was substituted by the prescriber. Cost was the most important factor taken into consideration about generic substitution (92% for prescribers; 83% for patients and 82% for pharmacists). CONCLUSIONS: Our findings demonstrated that healthcare providers as well as the drug consumers have insufficient knowledge about generic drugs. Therefore, they should be better educated with respect to generic substitution.
Keywords: Turkey; Health Knowledge, Attitudes, Practice; Physicians; Pharmacists; Drugs, Generic